Effect of gender on the leaf morphological diversity in Pistacia lentiscus - Doghbage A.; Belhadj S.; Derridj A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Pistacia lentiscus (mastic tree) is very common in the Mediterranean region. In Algeria, Mastic tree is distributed in a wide range of habitats along the climatic gradient. We studied the factors that may shape its morphological, physiological, and genetic differentiation. For this purpose, we analyzed the morphological variability intra-population between male and female individuals of Pistacia lentiscus, by using leaf characters. In total, seven quantitative morphological variables were measured for the leaves. The statistical analysis (PCA), showed significant differences for the measured variables between male and female plants of Pistacia lentiscus.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)